Systematic review and meta-analysis to examine intrapartum interventions, and maternal and neonatal outcomes following immersion in water during labour and waterbirth - Priscilla J Hall; Claire Feeley; Ethel Burns; Jennifer Vanderlaan (BMJ Open)
Objectives Water immersion during labour using a birth pool to achieve relaxation and pain relief during the first and possibly part of the second stage of labour is an increasingly popular care option in several countries. It is used particularly by healthy women who experience a straightforward pregnancy, labour spontaneously at term gestation and plan to give birth in a midwifery led care setting. More women are also choosing to give birth in water. There is debate about the safety of intrapartum water immersion, particularly waterbirth. We synthesised the evidence that compared the effect of water immersion during labour or waterbirth on intrapartum interventions and outcomes to standard care with no water immersion. A secondary objective was to synthesise data relating to clinical care practices and birth settings that women experience who immerse in water and women who do not.Design Systematic review and meta-analysis.Data sources A search was conducted using CINAHL, Medline, Embase, BioMed Central and PsycINFO during March 2020 and was replicated in May 2021.Eligibility criteria for selecting studies Primary quantitative studies published in 2000 or later, examining maternal or neonatal interventions and outcomes using the birthing pool for labour and/or birth.Data extraction and synthesis Full-text screening was undertaken independently against inclusion/exclusion criteria in two pairs. Risk of bias assessment included review of seven domains based on the Robbins-I Risk of Bias Tool. All outcomes were summarised using an OR and 95% CI. All calculations were conducted in Comprehensive Meta-Analysis V.3, using the inverse variance method. Results of individual studies were converted to log OR and SE for synthesis. Fixed effects models were used when I2 was less than 50%, otherwise random effects models were used. The fail-safe N estimates were calculated to determine the number of studies necessary to change the estimates. Begg’s test and Egger’s regression risk assessed risk of bias across studies. Trim-and-fill analysis was used to estimate the magnitude of effect of the bias. Meta-regression was completed when at least 10 studies provided data for an outcome.Results We included 36 studies in the review, (N=157 546 participants). Thirty-one studies were conducted in an obstetric unit setting (n=70 393), four studies were conducted in midwife led settings (n=61 385) and one study was a mixed setting (OU and homebirth) (n=25 768). Midwife led settings included planned home and freestanding midwifery unit (k=1), alongside midwifery units (k=1), planned homebirth (k=1), a freestanding midwifery unit and an alongside midwifery unit (k=1) and an alongside midwifery unit (k=1). For water immersion, 25 studies involved women who planned to have/had a waterbirth (n=151 742), seven involved water immersion for labour only (1901), three studies reported on water immersion during labour and waterbirth (n=3688) and one study was unclear about the timing of water immersion (n=215).Water immersion significantly reduced use of epidural (k=7, n=10 993; OR 0.17 95% CI 0.05 to 0.56), injected opioids (k=8, n=27 391; OR 0.22 95% CI 0.13 to 0.38), episiotomy (k=15, n=36 558; OR 0.16; 95% CI 0.10 to 0.27), maternal pain (k=8, n=1200; OR 0.24 95% CI 0.12 to 0.51) and postpartum haemorrhage (k=15, n=63 891; OR 0.69 95% CI 0.51 to 0.95). There was an increase in maternal satisfaction (k=6, n=4144; OR 1.95 95% CI 1.28 to 2.96) and odds of an intact perineum (k=17, n=59 070; OR 1.48; 95% CI 1.21 to 1.79) with water immersion. Waterbirth was associated with increased odds of cord avulsion (OR 1.94 95% CI 1.30 to 2.88), although the absolute risk remained low (4.3 per 1000 vs 1.3 per 1000). There were no differences in any other identified neonatal outcomes.Conclusions This review endorses previous reviews showing clear benefits resulting from intrapartum water immersion for healthy women and their newborns. While most included studies were conducted in obstetric units, to enable the identification of best practice regarding water immersion, future birthing pool research should integrate factors that are known to influence intrapartum interventions and outcomes. These include maternal parity, the care model, care practices and birth setting.PROSPERO registration number CRD42019147001.